OP0070 Anti-TNF Therapy and Tuberculosis Risk in Rheumatic Diseases, Psoriasis, and IBD: A Pooled-Data Analysis of Randomized Controlled Trials. (23rd January 2014) - Bruzzese, V.; Lorenzetti, R.; Zullo, A.; Hassan, C.; Campo, S. M.
Abstract : Background: Treatment with tumor necrosis factor (TNF) antagonists has been recognized as a risk factor for active tuberculosis (TB), particularly for reactivation of latent infection. Objectives: To evaluate the risk of TB in patients with rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PA), psoriasis (P), and inflammatory bowel diseases (IBD), treated with anti-TNF in randomized clinical trials (RCTs). Methods: MEDLINE and Cochrane databases were searched to 31 March 2012 for RCTs evaluating Infliximab (IFX), Adalimumab (ADA), and Certolizumab (CER), the only three anti-TNF drugs used both for IBD and RA, AS, PA and P. Results were calculated by using fixed effects model and reported as pooled odd ratios. Results: Overall, 86 RCTs with a total of 22, 071 patients were considered, including 26 RCTs with 6, 352 IBD patients, 45 RCTs with 11, 638 rheumatic diseases (RA, AS, PA) patients, and 15 RCTs with 4, 081 psoriatic patients. A total of 34 cases of TB were reported in patients (n= 14, 478) who received anti-TNF therapy and none in controls (n = 7, 593) (p< 0.001). Of these, 29 cases were reported in patients with rheumatic diseases (p< 0.001), 5 in IBD patients (p = 0.023), and none in psoriatic patients. Eight TB cases occurred by using a single anti-TNF drug (8, 808 patients; OR: 9.9, CI 0.5-172.4), and 26 in RCTs by using an anti-TNF and Methotrexate combination (5, 644 patients; OR: 48.3, CI 2.9-793.7). No difference emerged among IFX, ADA, and CER for TB risk. Conclusions: Anti-TNF treatment significantly increases risk of TB infection. The risk seems to be particularly elevated in patients treated for rheumatic disease when a combination therapy with Methotrexate is used. Disclosure of Interest: None Declared